Metabolomic profiles and microbiota of GDM offspring: The key for future perspective? - Dessì, Angelica; Tognazzi, Chiara; Bosco, Alice; Pintus, Roberta; Fanos, Vassilios (Frontiers in Pediatrics, 2022)
Gestational diabetes mellitus (GDM), or any degree of glucose intolerance recognized for the first time during pregnancy, is one of the diseases that most frequently aggravates the course of gestation. Missed or late diagnosis and inadequate treatment are associated with high maternal and fetal morbidity, with possible short- and long-term repercussions. Estimates on the prevalence of GDM are alarming and have shown an increase in this disease of about 30% in the last 10-20 years. In addition, there is the negative influence of the SARS-CoV-2 emergency on the glycemic control of pregnant women, making the matter increasingly topical. To date, knowledge on the metabolic maturation of newborns is partial, however in light of the considerable progress of the theory of "developmental origins of health and disease", the delicate role of the intrauterine environment cannot be overlooked. In fact, due to the high plasticity of the early stages of development, some nutritional insults during fetal growth, including maternal hyperglycemia, are associated with a higher incidence of chronic diseases in adult life. In this context, the use of the metabolomic survey which allows to obtain a detailed phenotypic portrait through the dynamic detection of all metabolites in cells, tissues and different biological fluids could be very useful for the early diagnosis and prevention of complications. In fact, if on the one hand the diagnostic timing is optimized through the identification of specific metabolites, on the other hand, the detailed understanding of the altered metabolic pathways can allow better management and more careful monitoring, also from a nutritional profile, of the more fragile children. In this context, a further contribution derives from the analysis of the intestinal microbiota, the main responsible for the fecal metabolome, given its alteration in pregnancies complicated by GDM and the possibility of transmission to offspring. The purpose of this review is to analyze the available data regarding the alterations in the metabolomic profile and microbiota of the offspring of mothers with GDM in order to highlight future prospects for reducing GDM-related complications in the offspring.